MBKM Program: Young Culinary Entrepreneur (TKP) Know Spicy Krispy - Pramudita, Bintang; Prabowo, Cristiyanto Wisnu; Pramudita, Hadian (Eastasouth Institute, 2023)
Fast food is very popular and has become a trend for Indonesian people. Tofu is an energy source that is rich in carbohydrates. The tendency to consume modern food has become a trend for Indonesian people. Tofu is a type of food source of protein made from soybeans which is very popular and popular with Indonesian people. Tofu is also a processed soybean product which has a fairly wide market segment. This is proven by the existence of various types of tofu that are sold on the market, namely: sumedang tofu, filled tofu, and meatball tofu. Tofu is a healthy food that contains lots of nutrients, from protein to fiber. This food is useful for maintaining heart health, and optimizing brain function.